Caring Behavior of Nurses in a Hospital: a Descriptive Phenomenological Study - Nova Lina Langingi; Ma. Elizabeth Baua (Jurnal Multidisiplin Madani, 2023)
The caring behavior of the nurses is the core of professional nursing practice and the culture of the nursing profession that affects the quality of service, patient satisfaction, patient health, and well-being. This study aims to analyze the caring behavior of nurses in a private hospital in Manado, Indonesia. Philosophical underpinning based on Husserlian’s thought and descriptive phenomenological research design was used, with six participants in the hospital obtained through the snowball sampling technique. Collaizi's seven-step methodological interpretation was used in the analysis. This study found that nurses have seven caring behaviors: compassion, responsiveness, self-control, thoroughness, critical thinking, comforting, and educating. It is recommended that nurses maintain and improve their caring behavior, and for the next study, it is recommended to do the interview directly face-face